ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY DIMENSIONS ON PHARMACY CUSTOMER SATISFACTION KIMIA FARMA BATAM CENTER - Edwin Agung Wibowo; Tibrani Tibrani (University of Riau Kepulauan, 2022)
The purpose of this study was to determine the effect of physical evidence, reliability, responsiveness, assurance, and empathy to customer satisfaction at Kimia Farma Batam Center Pharmacy. The sample in this study were 98 Pharmacy customers at Apotek Kima Farma Batam Center. Tests in this study use the validity test, reliability test, multiple linear regression test, data normality test, multicollinearity test, heteroscedastity test, partial test, simultaneous test, and coefficient of determination test. From the test results obtained that the physical evidence variable has a positive and significant effect on customer satisfaction, with a calculated t value of 5.134 and a significance of 0.000. The reliability variable has a positive and very significant effect on customer satisfaction, with a t value of 5.149 and a significance of 0.000. The responsiveness variable has a positive and significant effect on customer satisfaction, with the value of t arithmetic is 2.256 and the significance of 0.026. The guarantee variable has a positive and significant effect on customer satisfaction, with the value of t arithmetic is 8.448 and the significance of 0.000. Empathy variable has a positive and significant effect on customer satisfaction, with a calculated t value of 9,289 and a significance of 0,000.